Who Gained from the Introduction of Free Universal Secondary Education in England and Wales? - Robert A. Hart; Mirko Moro; J. Elizabeth Roberts (Institute for the Study of Labor (IZA), 2016)
This paper investigates the introduction of free universal secondary education in England and Wales in 1944. It focuses on its effects in relation to a prime long-term goal of pre-war Boards of Education. This was to open secondary school education to children of all social backgrounds on equal terms. Adopting a difference-in-difference estimation approach, we do not find any evidence that boys and girls from less well-off home backgrounds displayed improved chances of attending selective secondary schools. Nor, for the most part, did they show increased probabilities of gaining formal school qualifications. One possible exception in this latter respect relates to boys with unskilled fathers.
Keywords: I21; I24; I28; 330; school qualifications; 1944 Education Act; free secondary education; family background